(untitled) (Indian Journal of Chemistry (IJC), 2025)
N’-(4-(tert-butyl)benzylidene)-1-(2-methoxyphenyl)-5-methyl-1H-pyrazole-4-carbohydrazide (3), was successfully obtained from substituted N-acyl hydrazide (1) and 4-tert- butyl benzaldehyde (2) via condensation reaction and subsequently purified. X-ray crystal structures of the synthesized compound (3) were determined. The molecular structure of the compound was further elucidated by the FT-IR, 1H and APT-13C NMRs, LC-MS-QTOF spectroscopic methods. The geometry derived from the X-ray experiments was compared with theoretical calculations using Hartree-Fock (HF) and density functional theory (DFT) using the 6 - 31G+(d,p) basis set to validate the experimental results. The results showed good agreement between the calculated and experimental structures of the compound. In addition, Molecular Electrostatic Potential (MEP), Frontier Molecular Orbital (FMO), and Hirshfeld surface analyses were performed to gain further insight into the molecular structure. Thermal analysis and nonlinear optical (NLO) characterization were integral to this comprehensive study.